Atypical angiopoietin-like protein that regulates ANGPTL3 - Quagliarini, Fabiana; Wang, Yan; Kozlitina, Julia; Grishin, Nick V; Hyde, Rhonda; Boerwinkle, Eric; Valenzuela, David M; Murphy, Andrew J; Cohen, Jonathan C; Hobbs, Helen H (Proceedings of the National Academy of Sciences - PNAS, 2012)
Angiopoietin-like proteins (ANGPTLs) play major roles in the trafficking and metabolism of lipids. Inactivation of ANGPTL3, a gene located in an intron of DOCK7, results in very low levels of LDL-cholesterol (C), HDL-C and triglyceride (TAG). We identified another ANGPTL family member, ANGPTL8, which is located in the corresponding intron of DOCK6. A variant in this family member (rs2278426, R59W) was associated with lower plasma LDL-C and HDL-C levels in three populations. ANGPTL8 is expressed in liver and adipose tissue, and circulates in plasma of humans. Expression of ANGPTL8 was reduced by fasting and increased by refeeding in both mice and humans. To examine the functional relationship between the two ANGPTL family members, we expressed ANGPTL3 at physiological levels alone or together with ANGPTL8 in livers of mice. Plasma TAG level did not change in mice expressing ANGPTL3 alone, whereas coexpression with ANGPTL8 resulted in hypertriglyceridemia, despite a reduction in circulating ANGPTL3. ANGPTL8 coimmunoprecipitated with the N-terminal domain of ANGPTL3 in plasma of these mice. In cultured hepatocytes, ANGPTL8 expression increased the appearance of N-terminal ANGPTL3 in the medium, suggesting ANGPTL8 may activate ANGPTL3. Consistent with this scenario, expression of ANGPTL8 in Angptl3(-/-) mice failed to promote hypertriglyceridemia. Thus, ANGPTL8, a paralog of ANGPTL3 that arose through duplication of an ancestral DOCK gene, regulates postprandial TAG and fatty acid metabolism by controlling activation of its progenitor, and perhaps other ANGPTLs. Inhibition of ANGPTL8 provides a new therapeutic strategy for reducing plasma lipoprotein levels.